Rapid determination of total polyphenolic content in tea samples based on caffeic acid voltammetric behaviour on a disposable graphite electrode. (15th April 2015) - David, Iulia Gabriela; Bizgan, Ana-Maria Cristina; Popa, Dana Elena; Buleandra, Mihaela; Moldovan, Zenovia; Badea, Irinel Adriana; Tekiner, Tuğçe Ayça; Basaga, Huveyda; Ciucu, Anton A.
Highlights: The voltammetric behaviour of caffeic acid at a disposable pencil graphite electrode was studied. A simple and sensitive voltammetric method for caffeic acid determination was developed. The method is a cheap tool for rapid total polyphenolic content analysis of teas (mg CAE/g tea). The developed voltammetric method is as precise as the Folin–Ciocalteu method. Abstract: The present paper describes the voltammetric behaviour and the quantitative determination of caffeic acid (CA) on a disposable pencil graphite electrode (PGE). The anodic peak current of CA recorded by differential pulse voltammetry (DPV) varies linearly with CA concentration in the range 1 × 10 −7 –3 × 10 −3 M. The detection and quantification limits were 8.83 × 10 −8 M and 2.94 × 10 −7 M caffeic acid, respectively. The mean recoveries of CA from Turkish green, white and black teas were 98.30%, 99.57% and 91.46%. For these three tea types the corresponding total polyphenolic contents (TPCs) evaluated by DPV on PGE were 35.81, 34.59 and 31.21 mg caffeic acid equivalent/g tea, respectively. These TPC values were in good accordance with those obtained by the Folin–Ciocalteu method. The developed DPV on PGE method constitutes a simple and inexpensive tool for the rapid assessment of TPC of tea samples.